Encapsulation of anthocyanins from purple corn cob via antisolvent precipitation: Effect of pH and zein/gum arabic ratio on the antioxidant activity, particle size and thermal stability - Johan Mendoza; Omar Peñuñuri-Miranda; María d.C. Valdez-Cárdenas; Carmen O. Melendez-Pizarro; Daniel Lardizabal-Gutiérrez; Francisco Paraguay-Delgado; Armando Quintero-Ramos (Food Hydrocolloids for Health)
This study evaluates the effects of pH levels and Zein/Gum Arabic (Z/GA) ratios on key encapsulation parameters of an anthocyanin-rich extract (ARE) derived from purple corn cob, using the antisolvent precipitation method. Parameters analyzed include encapsulation efficiencies for anthocyanins (%AEE) and polyphenols (%PEE), nanoparticle size, polydispersity index, ζ-potential, and thermal stability at 80 and 180 °C. Particles without GA showed poor stability and low %AEE, particularly at lower pH. Conversely, the addition of GA significantly enhanced encapsulation efficiency, especially under acidic conditions (pH 2–4), and improved the particle size uniformity. At Z/GA ratio of 1:1, GA played a crucial role in stabilizing nanoparticles, effectively preventing aggregation even when the net particle charge was near to zero. Characterization by SEM, FTIR and TGA confirmed the morphological, structural, and thermal properties of the encapsulated particles. Thermal stability tests demonstrated that encapsulated anthocyanins exhibited significantly improved resistance to thermal degradation, with half-life extended up to threefold compared to unencapsulated counterparts. These results highlight the potential of encapsulating ARE from purple corn cob in Z/GA matrices as a method to preserve anthocyanins functionality, improve their thermal stability during food processing, and enhance application in food systems. Additionally, this approach offers a sustainable alternative, adding value to agricultural by-products and promoting waste valorization in the food industry. However, further research on scalability, cost-effectiveness, and application in food processing systems are needed.